AN ANALYSIS PHRASE STRUCTURE RULES IN ANNETH SONG LYRICS - Rahmawati Rahmawati; Sinta Parulian Lumban Gaol; Novia Damayanti Br Hutabarat; Tina Pandiangan (Indonesian EFL Journal, 2022)
Â The purpose of this study was to determine the types of phrases and the rules of phrase structure in Anneth's song lyrics. Researchers also want to know the extent to which students' ability to know about phrases. Class IX students selected as participants consisted of 59 students at SMP Adventist 2 Medan. The data was obtained by providing questionnaires about what phrases are, types of phrases, and what are sentences. The researcher introduced the types of phrases in the form of tables and tree diagrams. The table form is in the form of the first to the last lyrics, while the tree diagram is made by dividing the large categories into smaller levels, each word in the song lyrics is adjusted to the contents of the table so that it can form phrases and sentences. The types of phrases contained in the song are noun phrase (NP), verb phrase (VP), adverb phrase (AdvP), adjective phrase (AP), and preposition phrase (PP). The basic phrase structure rules in the song are: S : NP (Aux) VP, NP : {Det (Adj) N, Pro, N (PP)}, VP : V (NP) (PP) (Adv), AP : A(PP), AdvP : Aux (AdvP), PP : P (NP).Keywords: phrase; phrase structure rules; song lyrics.